2005
DOI: 10.4049/jimmunol.175.4.2174
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-Induced Inhibition of YY1 and Bcl-xL Expression in Ramos Non-Hodgkin’s Lymphoma Cell Line via Inhibition of NF-κB Activity: Role of YY1 and Bcl-xL in Fas Resistance and Chemoresistance, Respectively

Abstract: Rituximab treatment of B non-Hodgkin’s lymphoma (NHL) cell lines inhibits the constitutive NF-κB activity and results in the sensitization of tumor cells to both chemotherapy and Fas-induced apoptosis. Cells expressing dominant active IκB or treated with NF-κB-specific inhibitors were sensitive to both drugs and Fas agonist mAb (CH-11)-induced apoptosis. Down-regulation of Bcl-xL expression via inhibition of NF-κB activity correlated with chemosensitivity. The direct role of Bcl-xL in chemoresistance was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 42 publications
(44 reference statements)
5
99
0
Order By: Relevance
“…Resistance to apoptosis accompanied by uncontrollable cell division could promote growth of tumor mass in the nude mice. This working model is also supported by the knowledge that a G 2 /M checkpoint defect promotes tumorigenesis (3) and that there is close association of up-regulation of three such antiapoptotic proteins, Bcl-xL, XIAP, and cIAP2, with constitutive activation of NF-B and resistance to apoptosis in a variety of human malignancies (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 73%
“…Resistance to apoptosis accompanied by uncontrollable cell division could promote growth of tumor mass in the nude mice. This working model is also supported by the knowledge that a G 2 /M checkpoint defect promotes tumorigenesis (3) and that there is close association of up-regulation of three such antiapoptotic proteins, Bcl-xL, XIAP, and cIAP2, with constitutive activation of NF-B and resistance to apoptosis in a variety of human malignancies (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 73%
“…In previous findings, we have reported that Fas expression is negatively regulated by the transcription repressor YY1 via binding of YY1 to the silencer region of the Fas promoter (19). We have also reported that inhibition of NF-nB correlated with inhibition of YY1 (20). Because there is a putative binding site for YY1 in the DR5 promoter, we hypothesized that chemotherapeutic drugs may inhibit YY1 expression or its DNA-binding activity, resulting in up-regulation of DR5 expression and sensitization to TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 73%
“…Consistent with our findings here, Palayoor et al (30) have reported that NF-nB is constitutively activated in the hormone-refractory prostate cancer cell lines PC-3 and DU145. The suppression of NFnB survival signaling by various agents has been shown to sensitize different neoplasms, including prostate tumors, to the antitumor effects of TRAIL (20,31) via several mechanisms (24,32,33). However, many antineoplastic agents, including anthracyclines, paclitaxel, and Vinca alkaloids, have been shown to induce NF-nB activation in human lung adenocarcinoma and other cell lines mainly via activation of protein kinase C, resulting in InBa degradation (34 -36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that treatment of prostate tumor and non-Hodgkin's B cell lymphoma (B-NHL) cell lines with DETANONOate reduced the NFκB DNA-binding activity attributed to S-nitrosylation of the NFκB p50 subunit by NO. 33,42,43 The above observations suggest that NO is a potent NFκB inhibitor and that DETANONOate mediates its anti-metastatic properties, in part, via suppression of NFκB signaling.…”
Section: Discussionmentioning
confidence: 98%